Efficient hydrogen gas production from molasses in hybrid anaerobic-activated sludge-rotating biological contactor - Mohammadi, Mahin; Mohammadi, Parviz; Karami, Nasim; Barzegar, Akbar; Annuar, Mohamad Suffian Mohamad (Elsevier, 2019)
A hybrid anaerobic activated sludge and rotating biological contactor (AnAS-RBC) reactor with sludge return was investigated for biological hydrogen production from molasses by a mixed culture of hydrogen-producing bacteria via a dark fermentation process. The pH was not controlled during the experiments. The effects of organic loading rate (OLR) and disk rotational speed (DRS) on process performance were studied using response surface methodology. Both OLR and DRS showed significant effects on all process responses. High levels of DRS were found favorable for efficient process. Optimal mixing of the bacterial culture contributed towards higher acetate production resulting in higher hydrogen production. The highest hydrogen production (168 mL/g COD) was achieved by applying OLR and DRS of 23 g/L.d and 30 rpm, respectively. In this study, the highest percentage of hydrogen in biogas produced was 87% in hydraulic retention time of 12 h. © 2018 Hydrogen Energy Publications LLC